Southern Ocean anthropogenic carbon sink constrained by sea surface salinity - Terhaar, Jens; Frölicher, Thomas L.; Joos, Fortunat (Science Advances, 2021)
Observed sea surface salinity constrains past and future anthropogenic carbon uptake in the Southern Ocean.